1982
DOI: 10.1042/bj2040061
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and morphological modifications in rabbit Achilles tendon during maturation and ageing

Abstract: 1. Achilles tendons of foetal, newborn, adult and old rabbits were examined by electron microscopy after staining by conventional methods or with the periodate/silver/methenamine technique. 2. The mean diameter of collagen fibrils increased with age whereas silver/methenamine-positivity became less evident. 3. Biochemical analyses showed a great decrease of the concentration of glycoproteins and galactosamine-containing glycosaminoglycans. 4. Collagen content increased with maturation and ageing of the tissue.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 23 publications
1
21
1
1
Order By: Relevance
“…One study suggests that aging produces stiffer and stronger tendons [50], but other investigations led to the opposite conclusion [44,54] or showed no effect of aging on most of the mechanical properties of the tendon [16]. In animals, tenocyte metabolism changes with increasing age [13], and these changes are accompanied by morphologic changes [6]. In humans, similar matrix alterations have been reported [31,52].…”
Section: Introductionmentioning
confidence: 90%
“…One study suggests that aging produces stiffer and stronger tendons [50], but other investigations led to the opposite conclusion [44,54] or showed no effect of aging on most of the mechanical properties of the tendon [16]. In animals, tenocyte metabolism changes with increasing age [13], and these changes are accompanied by morphologic changes [6]. In humans, similar matrix alterations have been reported [31,52].…”
Section: Introductionmentioning
confidence: 90%
“…Therefore, these modifications are probably important for protein-protein and protein-cell interactions. The extent of hydroxylation of lysine residues and glycosylation of hydroxylysine residues is known to be age-and tissue-specific and especially high levels are found in embryonic tissues (Bateman et al, 1996;Cetta et al, 1982;Kielty and Grant, 2002;Kivirikko and MyllylĂ€, 1979;Kivirikko et al, 1992). Furthermore, the number of hydroxylysine and glycosylated hydroxylysine residues varies among the various collagen types; for instance type IV collagen found in basement membranes (BM) and type VI collagen found in blood vessels have large numbers of these modifications (Ayad et al, 1998;Kivirikko et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…A small amount of glycosaminoglycans is associated with fibrils of larger diameter and a greater global synthesis of collagen. 12,86 Fibrillogenesis in situ has been studied by Birk et al 87 and Birk, Nurminskaya and Zycband. 88 The transformation of the smooth vacuoles may occur before they reach the surface of the cell, resulting in a loss of their content inside the cytoplasm of the fibroblast which would then contain fine dense granular substance among membrane residues.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Over the last 50 years there have been many studies of the extracellular formation of collagen, [17][18][19][20][21] but its intracellular formation and excretion to the extracellular matrix have not been investigated in depth. [22][23][24][25][26][27][28][29] Schwann 30 suggested that collagen fibres arose within fibroblasts and were released by splitting away from the cytoplasm, but according to Virchow 31 fibroblasts secrete a soluble substance which is built into collagen fibres in the extracellular space.…”
mentioning
confidence: 99%